PENERAPAN METODE INKUIRI TERHADAP KEMAMPUAN MENGANALISIS UNSUR INTRINSIK DALAM NOVEL â€œ9 SUMMERS 10 AUTUMNSâ€ KARYA IWAN SETYAWAN OLEH SISWA KELAS IX-3 SMP NEGERI 7 MEDAN TAHUN PEMBELAJARAN 2017/2018 - Ahsanul Husna (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The purpose of this study was to describe the students' ability to analyze the intrinsic elements in Iwan Setyawan's novel "9 Summers 10 Autumns" before using the inquiry method. This type of research is one group pretest posttest design. The population in the study of students of class IX-3 SMP Negeri 7 Medan. The sample in this study were 32 students of class IX-3 SMP Negeri 7 Medan. The inquiry method is in the sufficient category, this can be seen at an average value of 62.96. Hypothesis testing is tcount> ttable (9.14> 1.67). It can be concluded that there is a significant influence in the application of the inquiry method on the ability to analyze the intrinsic elements of the novel by students of class IX-3 SMP Negeri 7 Medan in the 2017â€“2018 academic year